A case of ameloblastic fibroma - NOMA, Hiroyasu; HAYASHI, Hideaki; SHIMONO, Masaki; SEKIKAWA, Yoshiaki; YAJIMA, Yasutomo; KUKIMOTO, Yoshiaki; KAKIZAWA, Takashi; SHIMIZU, Souichi; YAMANE, Hideki (Japanese Journal of Oral and Maxillofacial Surgery, 1986)
The ameloblastic fibroma is an uncommon tumor which is known as one of the odontogenic mixed tumors. Our case of ameloblastic fibroma of the right mandibular molar in a male (11 year-old) was referred to our hospital because the first right mandibular permanent molar delayed eruption. The treatment was simple exision under local anesthesia. After the operation the patient has been checked for a further 1 year 4 months. The first permanent molar has erupted and there is no sign of recurrence. The ameloblastic fibroma have been reported on 35 occasions in the Japanese literature and we added one case. We reviewed and discussed the 36 cases of ameloblastic fibroma with this report.